Incidence of Urethrocutaneous Fistula Formation in Patients Undergoing Urethroplasty with and without Stent for Hypospadias: Urethrocutaneous Fistula Formation in Patients Undergoing Urethroplasty for Hypospadias - Shafee, Saira; Chishti, Muhammad Kashif; Shamrez, Ambar; Hanif, Muhammad Amir; Khan, Mahreen Zahra; Rasool, Saif Ur; Khan, Muhammad Nauman (Pakistan Journal of Health Sciences, 2026)
Hypospadias is a common congenital anomaly in boys, and urethrocutaneous fistula (UCF) remains a frequent complication after urethroplasty. The routine use of urethral stents is still debated, especially in low-resource settings such as Pakistan. Objectives: To compare UCF incidence between stented and stentless urethroplasty and to identify factors associated with fistula formation. Methods: A randomized controlled trial was carried out in the Department of Pediatric Surgery, Children’s Hospital Multan, from 10 May to 10 November 2025. A total of 110 boys aged 1–12 years with distal or mid-penile hypospadias were randomized to stent urethroplasty (Group A, n=55) or stentless urethroplasty (Group B, n=55). Data were analyzed using t-test, Mann–Whitney U test, chi-square test, and binary logistic regression with p<0.05 as significant. Results: Mean age was 6.1±2.6 years in Group A and 5.7±2.9 years in Group B. Overall UCF incidence was 10% (11/110), higher in Group A than Group B (14.5% vs 5.5%; p=0.046). At 12 weeks, UCF occurred in 14.5% of stented repairs and 5.5% of stentless repairs (p=0.046). Postoperative infection and longer operative duration were independently associated with UCF. Hospital stays, a secondary outcome, were longer in the stented group. Conclusions: In this cohort, stentless urethroplasty demonstrated a lower 12-week UCF incidence compared with stented repair.